Plant-based expression platforms to produce high-value metabolites and proteins - Kulshreshtha, Aditya; Sharma, Shweta; Padilla, Carmen S.; Mandadi, Kranthi K. (Frontiers in Plant Science, 2022)
Plant-based heterologous expression systems can be leveraged to produce high-value therapeutics, industrially important proteins, metabolites, and bioproducts. The production can be scaled up, free from pathogen contamination, and offer post-translational modifications to synthesize complex proteins. With advancements in molecular techniques, transgenics, CRISPR/Cas9 system, plant cell, tissue, and organ culture, significant progress has been made to increase the expression of recombinant proteins and important metabolites in plants. Methods are also available to stabilize RNA transcripts, optimize protein translation, engineer proteins for their stability, and target proteins to subcellular locations best suited for their accumulation. This mini-review focuses on recent advancements to enhance the production of high-value metabolites and proteins necessary for therapeutic applications using plants as bio-factories.